2017
DOI: 10.1186/s40645-016-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of irreversible reactions and deformation: a case of hydrofracturing in the rodingite–serpentinite system

Abstract: The interplay of irreversible reactions and deformation during regional metamorphism was analyzed in the reaction zones between rodingite and serpentinite. Rodingites are leucocratic rocks found commonly in serpentinites and are considered metasomatic products of Ca-rich fluid. Rodingites occur ubiquitously in serpentinite from the Nomo metamorphic rocks, western Kyushu, a Cretaceous accretionary complex of greenschist to epidote-amphibolite facies condition. We used the singular value decomposition (SVD) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Metasomatic reaction zones are found at the contact between schist or rodingite pods and the surrounding serpentinite. Such reactions between serpentinite and siliciccalcic lithologies that form tremolite, talc, diopside and chlorite are extensively documented in the literature (Cronshaw, 1923;Read, 1934;Nishiyama, 1990;Boschi et al, 2006;Nishiyama et al, 2017). In the Livingstone Fault, metasomatic reactions resulted in the transformation of foliated serpentinite into a highly indurated metasomatic fault rock largely consisting of networks of tremolite veins (Fig.…”
Section: Mixed Rheology In Plate-boundary-scale Serpentinite Shear Zonesmentioning
confidence: 87%
“…Metasomatic reaction zones are found at the contact between schist or rodingite pods and the surrounding serpentinite. Such reactions between serpentinite and siliciccalcic lithologies that form tremolite, talc, diopside and chlorite are extensively documented in the literature (Cronshaw, 1923;Read, 1934;Nishiyama, 1990;Boschi et al, 2006;Nishiyama et al, 2017). In the Livingstone Fault, metasomatic reactions resulted in the transformation of foliated serpentinite into a highly indurated metasomatic fault rock largely consisting of networks of tremolite veins (Fig.…”
Section: Mixed Rheology In Plate-boundary-scale Serpentinite Shear Zonesmentioning
confidence: 87%
“…Blocks of Type B consist of garnet-bearing epidote-blueschist-barroisite rock, meta-hornblendite, albitite, zoisite rock, rodingite, omphacite-bearing metagabbro, omphacitite, and jadeitite. Rodingite (grossular + clinozoisite + diopside) is very rare in the Nishisonogi unit, whereas it is ubiquitous in the Nomo unit (Fukuyama et al, 2014;Nishiyama et al, 2017). These features of the serpentinite mélange in this region indicate that tectonic mixing of various rocks occurred in a narrow serpentinite channel within a subduction zone under the ductile condition together with extensive metasomatism.…”
Section: Serpentinite Mélangementioning
confidence: 95%
“…Fukuyama et al (2014) reported the U-Pb ages of zircons from rodingites in serpentinites associated with the Sanwa Formation as 108-105 Ma, indicating that the formation of rodingites predates the peak metamorphism of the Sanwa Formation. The coherent schists in the Sanwa Formation have undergone greenschist to epiote-amphibolite facies metamorphism; only rocks associated with the serpentinite in the Sanwa Formation represents epidote-blueschist facies metamorphism according to the occurrence of omphacite and magnesio-riebeckite (Nishiyama and Miyazaki, 1987;Miyazaki and Nishiyama, 1989;Nishiyama et al, 2017). The Nomozaki Formation and the older metagabbros have undergone pum- pellyite-actinolite facies metamorphism (Miyazaki and Nishiyama, 1989).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear combination of the two solutions provides a general solution (cf. Nishiyama et al, 2017), which is described as R6, 9, 12, 15, and 18 in Table 3. We obtained the ranges of the variable so that the solutions have proper signs for the stoichiometric coefficients consistent with the microstructure, that is, 0.30 < p < 0.64 (R6), 0.39 < q (R9), 0.31 < r < 0.67 (R12), and 0.27 < t < 0.53 (R18).…”
Section: Corona-forming Net Reactionmentioning
confidence: 99%